2008
DOI: 10.1074/jbc.m802869200
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Cardiac Hypertrophy via AMP-activated Protein Kinase and Akt

Abstract: Whereas studies involving animal models of cardiovascular disease demonstrated that resveratrol is able to inhibit hypertrophic growth, the mechanisms involved have not been elucidated. Because studies in cells other than cardiomyocytes revealed that AMP-activated protein kinase (AMPK) and Akt are affected by resveratrol, we hypothesized that resveratrol prevents cardiac myocyte hypertrophy via these two kinase systems. Herein, we demonstrate that resveratrol reduces phenylephrine-induced protein synthesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
183
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(198 citation statements)
references
References 40 publications
14
183
1
Order By: Relevance
“…Consistent with previous studies,7, 25 Rev substantially decreased the size of cardiomyocytes. Results from the current study showed that the dosage (10 μmol/L of Rev) markedly reduced the size of cardiomyocytes in vitro (Figure 1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies,7, 25 Rev substantially decreased the size of cardiomyocytes. Results from the current study showed that the dosage (10 μmol/L of Rev) markedly reduced the size of cardiomyocytes in vitro (Figure 1).…”
Section: Resultssupporting
confidence: 93%
“…In a recent study, Jason et al. disclosed that Rev exerted antihypertrophic effects by activating AMPK by LKB1 and inhibiting Akt, thus suppressing protein synthesis and gene transcription in pathological cardiac hypertrophy 25. The present study yielded several novel findings about the antihypertrophic effects of Rev.…”
Section: Discussionsupporting
confidence: 55%
“…Conversely, reduced LKB1 expression and/or activity has been shown in the hypertrophied hearts of various transgenic mouse models (9,10), suggesting that pathological inhibition of LKB1 activity may be an important contributor to the hypertrophic process. In agreement with this, oxidative stress-mediated inhibition of LKB1 in hypertensive rats also appears to promote prohypertrophic signaling (11). However, despite the potential importance of LKB1 activity in terms of regulating cardiac hypertrophy, very few studies have specifically investigated LKB1 signaling in the heart and its role in atrial and ventricular development and remodeling.…”
mentioning
confidence: 78%
“…Resveratrol affects activities of a number of proteins involved in aging, such as sirtuins and PGC-1α, to exert beneficial effects on health and lifespan (Pirola and Frojdo 2008). Numerous studies have revealed health benefits of resveratrol supplementation, including delayed decline of age-related cognitive function, improved pancreatic β-cell function, and reduced cardiac hypertrophy in rodent models (Pearson et al 2008;Lee et al 2011;Chan et al 2008;Baur 2010). However, the effect of resveratrol on lifespan and the underlying mechanisms remain controversial.…”
Section: Introductionmentioning
confidence: 99%